Anomalous fluctuations in homogeneous fluid phase of active Brownian particles - Yuta Kuroda; Hiromichi Matsuyama; Takeshi Kawasaki; Kunimasa Miyazaki (Physical Review Research, 2023)
Giant number fluctuations (GNF) are an anomaly universally observed in active fluids with polar or nematic order. In this paper, we show that GNF arise in the fluid phase of active Brownian particles (ABP), where the polar order is absent. GNF in ABP extends over a large but finite length which characterizes the growing velocity correlations. To suppress unwanted phase separation and allow ones to explore the disordered fluid phase at large activities, we impart the inertia, or the mass, to the ABP. A linearized hydrodynamic theory captures our findings, but only qualitatively. We find numerically a nontrivial scaling relation for the density correlation function, which the linearized theory cannot explain. The results suggest ubiquitousness of the anomalous fluctuations even in the disordered homogeneous fluid phase in the absence of the directional order.